2020
DOI: 10.13057/biodiv/d210728
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic and rhizosphere bacteria from pineapple (Ananas comosus) plant in semi-arid ecosystem

Abstract: Abstract. Putrie RFW, Aryantha INP, Iriawati, Antonius S. 2020. Diversity of endophytic and rhizosphere bacteria from pineapple (Ananas comosus) plant in semi-arid ecosystem. Biodiversitas 21: 3084-3093. The natural environment majorly influences plant microbiome diversity, in terms of endophytic and rhizobacteria. Pineapple (Ananas comosus L. Merr) has been identified as one of host plants with a capacity to grow in semiarid ecosystems. The intrinsic microbial symbiont composition is recognized in a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…All the isolates were maintained and analyzed for antifungal and antibacterial potentialities. Putrie et al (2020) found that the major microorganisms in the rhizospheric soil are actinobacteria. Also, Khamna et al (2009) demonstrated that microorganisms from the rhizosphere are most ideal for controlling plant pathogens that's why we have explored rhizospheric soil.…”
Section: Screening Of Antagonistic Isolatesmentioning
confidence: 99%
“…All the isolates were maintained and analyzed for antifungal and antibacterial potentialities. Putrie et al (2020) found that the major microorganisms in the rhizospheric soil are actinobacteria. Also, Khamna et al (2009) demonstrated that microorganisms from the rhizosphere are most ideal for controlling plant pathogens that's why we have explored rhizospheric soil.…”
Section: Screening Of Antagonistic Isolatesmentioning
confidence: 99%
“…However, the relationship between endophytes and rhizosphere microorganisms is still unclear. Current studies have shown that the microbiome of cotton changes with space and time and affects availability of soil nitrogen, thereby affecting the growth and reproduction of plant ( Zhang et al, 2011 ; Tian and Zhang, 2017 ; Moronta-Barrios et al, 2018 ; Lu et al, 2020 ; Putrie et al, 2020 ). Therefore, the changes in microbiome may affect healthy of cotton.…”
Section: Introductionmentioning
confidence: 99%
“…The major influences that the rhizospheric microorganisms have, nowadays, become an important tool to preserve plant health by an eco-friendly approach. It has been established that actinobacteria are the major microorganism in the rhizosphere and are the most ideal for controlling plant pathogens (Putrie et al, 2020). For these reasons, rhizospheric actinomycetes have been chosen to be explored for antagonists screening.…”
Section: In Vivo Bioassay Against S Scabies On Radish Seedlingmentioning
confidence: 99%